1998
DOI: 10.1111/j.1439-0264.1998.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Tongue of a Male Formosan Serow (Capricornis crispus swinhoei)

Abstract: The morphology of the tongue of an adult Formosan serow was examined to compare it with that of the Japanese serow by macroscopical and scanning electron microscopical observations. The tongue was 13.5 cm in length and 82 g in weight. The apex showed a U-shaped outline. There were 340 fungiform papillae and 23 vallate papillae on both sides. Filiform, fungiform, conical and vallate papillae were found. Annular pads surrounding the vallate papillae were poorly developed. No lenticular or foliate papillae were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
93
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(111 citation statements)
references
References 4 publications
15
93
3
Order By: Relevance
“…The fungiform papillae were more densely distributed on the tip and ventral surface of the lingual apex in Japanese serow, Formosan serow, blackbuck and Barbary sheep, and the papillae were smaller than that of the body (Funato et al, 1985;Atoji et al, 1998;Emura et al, 1999Emura et al, , 2000a. These reports coincide with the findings on the roan antelope.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The fungiform papillae were more densely distributed on the tip and ventral surface of the lingual apex in Japanese serow, Formosan serow, blackbuck and Barbary sheep, and the papillae were smaller than that of the body (Funato et al, 1985;Atoji et al, 1998;Emura et al, 1999Emura et al, , 2000a. These reports coincide with the findings on the roan antelope.…”
Section: Discussionmentioning
confidence: 60%
“…Atoji et al (1998) observed filiform papillae and conical papillae, and reported that the filiform papillae have secondary papillae in the Formosan serow. Emura et al (1999Emura et al ( , 2000a) also observed similar filiform papillae in the blackbuck and Barbary sheep.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Extensive morphologic research has also been presented on the filiform papillae in other ruminant species and breeds, including Formosan serows (Atoji et al, 1998), Blackbucks (Emura et al, 1999), Barbary sheep (Emura et al, 2000), Saanen goats (Kurtul & Atalgın, 2008), goitered gazelles (Harem et al, 2011), chital deer (Erdogan & Pérez, 2014), giraffes (Emura et al, 2013), one-humped camels (El Sharaby et al, 2012), and Bactrian camels (Eerdunchaolu et al, 2001). These previous works have reported on the orientations, distributions, appearances, ultrastructures and functions of such papillae.…”
Section: Introductionmentioning
confidence: 99%
“…The types of lingual papillae and their distribution have been widely investigated by scanning electron microscopy in various species, including the horse [4], chital deer [6], cattle [7][8][9], serow [10,11], buffalo [12], Saanen goat [13], camel [14], roan antelope [15], and donkey [16].…”
mentioning
confidence: 99%